Prediksi Jumlah Produksi Tempe Kopti Menggunakan Logika Fuzzy Metode Mamdani PRIMKOPTI Serang - Andi Irawan; Ibrahim Ajie; Firnando Island R.; Harsiti Harsiti (Universitas Serang Raya, 2019)
Capital is one of the problems faced by tempe producers, in each production, tempe producers issue capital that is erratic in order to influence. The level of production of tempeh it produces. In this study we will discuss how the application of fuzzy logic to the variable number of soybeans and the amount of yeast to predict the amount of tempe production. Data analysis was done by the mamdani method to find out the number of tempeh produced by craftsmen. The results of this study are in the form of three variables, namely 95 Kg of soybeans, 70 yeasts of spoonful and 487 pieces of tempe produced.